PROTOTYPE KNOWLEDGE MANAGEMENT SYSTEM UNTUK MENINGKATKAN PENYULUHAN KELUARGA BERENCANA BERBASIS ANDROID:STUDI KASUS BADAN PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK DAN KELUARGA BERENCANA KOTA BEKASI - Nurdiana Handayani (University of Muhammadiyah Tangerang, 2017)
The management of knowledge (knowledge management) is very important in an institution or organization to acquire and share knowledge (knowledge sharing) in order to develop the human resource potential and manage the company's assets or intellectual institutions, thus becoming close attention of Badan Pemberdayaan Perempuan, Perlindungan Anak dan Keluarga Berencana (BP3AKB) Bekasi. The purpose of this study was to determine the extent of the influence of the knowledge management system of knowledge in the KB extension outreach activities, and building a knowledge management system application that can assist employees in planning extension activities online that can be accessed by android smartphone, which is expected to increase the productivity of employees . The method of this research is descriptive quantitative method which is supported by The Most Admired Knowledge Enterprise (MAKE), and a model of knowledge management system knowledge management system architecture using Amrit Tiwana. The results of this study based on questionnaires to the application of the android-based knowledge management system for employees that are on the 3:40 to 4:19 interval, the average value of the entire statement at 4:00 is well received.Â Keywords: Knowledge Management, Activity Counseling KB, MAKE, Architecture Knowledge Managemet System Amrit Tiwana, Android application.